A Conserved Basal Transcription Factor Is Required for the Function of Diverse TAL Effectors in Multiple Plant Hosts - Huang, Renyan; Hui, Shugang; Zhang, Meng; Li, Pei; Xiao, Jinghua; Li, Xianghua; Yuan, Meng; Wang, Shiping (Frontiers in Plant Science, 2017)
Many Xanthomonas bacteria use transcription activator-like effector (TALE) proteins to activate plant disease susceptibility (S) genes, and this activation contributes to disease. We recently reported that rice basal transcription factor IIA gamma subunit, OsTFIIAγ5, is hijacked by TALE-carrying Xanthomonas oryzae infecting the plants. However, whether TFIIAγs are also involved in TALE-carrying Xanthomonas-caused diseases in other plants is unknown. Here, molecular and genetic approaches were used to investigate the role of TFIIAγs in other plants. We found that TFIIAγs are also used by TALE-carrying Xanthomonas to cause disease in other plants. The TALEs of Xanthomonas citri pv. citri (Xcc) causing canker in citrus and Xanthomonas campestris pv. vesicatoria (Xcv) causing bacterial spot in pepper and tomato interacted with corresponding host TFIIAγs as in rice. Transcriptionally suppressing TFIIAγ led to resistance to Xcc in citrus and Xcv in pepper and tomato. The 39th residue of OsTFIIAγ5 and citrus CsTFIIAγ is vital for TALE-dependent induction of plant S genes. As mutated OsTFIIAγ5V39E, CsTFIIAγV39E, pepper CaTFIIAγV39E, and tomato SlTFIIAγV39E also did not interact with TALEs to prevent disease. These results suggest that TALE-carrying bacteria share a common mechanism for infecting plants. Using TFIIAγV39E-type mutation could be a general strategy for improving resistance to TALE-carrying pathogens in crops.